2022
DOI: 10.17305/bjbms.2022.7504
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for breast cancer treatment in Bosnia and Herzegovina

Abstract: Breast cancer is the most common cancer among women. In Bosnia and Herzegovina, accurate data on the status of breast cancer are lacking due to the absence of a central registry. Multiple international guidelines imply that institutions that monitor breast cancer patients should have optimal therapeutic options for treatment. In addition, there have been several international consensus guidelines written on the management of breast cancer. Application of consensus guidelines have previously been demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…The flowchart of searching strategy and study selection is shown in Table 1. Forty‐seven articles were strongly in favour of performing SLNB in PrBC, 2,4,6,13–56 4 articles were partially in favour, 57–60 2 articles were partially against 61,62 and 10 articles were strongly against SLNB in PrBC patients 3,5,10,63–69 . Sub‐analysis based on type of study showed that out of 47 articles which were strongly in favour of SLNB, 11 were prospective cohorts or RCTs, 5 were retrospective case series or case reports, 25 were review articles and 6 articles were guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flowchart of searching strategy and study selection is shown in Table 1. Forty‐seven articles were strongly in favour of performing SLNB in PrBC, 2,4,6,13–56 4 articles were partially in favour, 57–60 2 articles were partially against 61,62 and 10 articles were strongly against SLNB in PrBC patients 3,5,10,63–69 . Sub‐analysis based on type of study showed that out of 47 articles which were strongly in favour of SLNB, 11 were prospective cohorts or RCTs, 5 were retrospective case series or case reports, 25 were review articles and 6 articles were guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, National Comprehensive Cancer Network (NCCN) guidelines endorse the safety of SLNB when the patient has given informed consent as several studies support that the technique can be safely performed 54 . The Guidelines for BC Management in Bosnia and Herzegovina, also released in 2020, explicitly advise against using lymphazurin and methylene blue during pregnancy and highly suggest the use 99mTc alone for SLNB mapping in PrBC 55 . Additionally, the Chinese Society of Breast Surgery (CSBrS) 56 and the Spanish Society of Medical Oncology have published similar recommendations in 2021 4 .…”
Section: Discussionmentioning
confidence: 99%